PENGARUH BRAND AMBASSADOR CINTA LAURA TERHADAP BRAND IMAGE FORE COFFEE - Nindhiya Salma Haura; Muria Putriana; Wina Puspita Sari; Nazwa Cendra Swari; Safiat Amaylia Putri; Nadia Zulmi; Yabes Edmund Macario Siburian; Kezia Revina Adelia Butarbutar (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2024)
This study investigates the impact of Cinta Laura's brand ambassador on Fore Coffee's brand image on Instagram, especially in the context of the rapidly growing coffee industry in Indonesia. As an agrarian country with a large population of coffee farmers, Indonesia faces intense competition in the coffee industry, forcing companies to implement effective marketing strategies. Involving brand ambassadors has become one of the commonly used strategies to strengthen brand image. In this study, simple random sampling techniques were used to ensure fair representation of the population of @fore.coffee's Instagram followers, which totaled 204k. A survey of 100 followers showed that Cinta Laura plays a key role in building Fore Coffee's positive image and has a strong influence through social media. The analysis results show that Cinta Laura's brand ambassador has a significant influence on Fore Coffee's brand image, with dimensions such as Visibility, Credibility, Attraction, and Power receiving high ratings. The t-test data shows a significant correlation between brand image and brand ambassador, with the correlation coefficient R confirming a very strong relationship. A total of 78.9% of brand image variables are influenced by brand Ambassadors, confirming Cinta Laura's vital role in increasing consumers' positive perceptions of Fore Coffee.